Beginning JavaScript with DOM scripting and Ajax - Ferguson, Russ; Heilmann, Christian (Expert's voice in Web development., 2013)
Beginning JavaScript with DOM Scripting and Ajax is an essential resource for modern JavaScript programming. This completely updated second edition covers everything you need to know to get up-to-speed with JavaScript development and add dynamic enhancements to web pages, right from the basics. As well as focusing on client-side JavaScript, you will also learn how to work with the Browser Object Model, the Document Object Model (DOM), how to use XML and JSON as well as communicate with service side scripts such as PHP. Find out how to: Construct good JavaScript syntax following modern coding practices Use JavaScript to communicate with the server and retrieve data Dynamically manipulate markup, validate forms and deal with images Debug applications using features inside the browser JavaScript is one of the most important technologies on the web. It provides the means to add dynamic functionality to your web pages and serves as the backbone of Ajax-style web development. Beginning JavaScript with DOM Scripting and Ajax will take you from being a JavaScript novice to work freely with this important technology - begin your JavaScript journey today!